Emergent Properties of an Art Talent Environment: An Empirical Study of Young Artists’ Experiences Within a Talent Development Program - Nørlem, Jakob; Stegeager, Nikolaj (International Journal for Talent Development and Creativity, 2022)
This article presents a study regarding a school for young talented artists. Within this context and based on systems thinking and a holistic ecological approach to talent development, the researchers seek to identify emergent contextual properties that enhance talent development. The research question of the study was “Which emergent properties support and influence talent development in the context of the Danish Talent Academy (DTA)?” The study is based on interviews with six young artists within different fields of art and five instructors. Furthermore, 12 hours of participant observation were conducted. Through a generic thematic analysis, six broad categories describing different emerging properties of the environment at DTA were identified. The paper argues that knowledge about emergent properties can help organizations improve artistic talent development and presents two specific strategies: 1) the organization’s ability to orient itself towards the emergent properties occurring every day; and 2) the organization’s ability to assist young artists in learning to reflect upon how emergent properties, at a certain point in time and in a certain context, may further liberate their artistic potential.